Advanced aerospace applications, volume 1 proceedings of the 29th IMAC, a conference on structural dynamics, 2011 - Proulx, Tom (Conference proceedings of the society for experimental mechanics series, 2011)
Advanced Aerospace Applications, Volume 1. Proceedings of the 29th IMAC, A Conference and Exposition on Structural Dynamics, 2011, the first volume of six from the Conference, brings together 32 contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on Aeroelasticity, Ground Testing, Dynamic Testing of Aerospace Structures, and Random Vibration.